2021
DOI: 10.3389/fgene.2021.763841
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Reveals Phenylpropanoid Biosynthesis Genes and Transcription Factors for Hevea brasiliensis Reaction Wood Formation

Abstract: Given the importance of wood in many industrial applications, much research has focused on wood formation, especially lignin biosynthesis. However, the mechanisms governing the regulation of lignin biosynthesis in the rubber tree (Hevea brasiliensis) remain to be elucidated. Here, we gained insight into the mechanisms of rubber tree lignin biosynthesis using reaction wood (wood with abnormal tissue structure induced by gravity or artificial mechanical treatment) as an experimental model. We performed transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
3
13
0
Order By: Relevance
“…Eleven genes that may encode transcription factors were identified, eight of which belong to the WRKY family. Our findings on differential expression of many genes encoding transcription factors are supported by previous investigations on other trees, such as rubber tree ( Meng et al, 2021 ) and Populus tomentosa ( Chen et al, 2015 ). In P. tomentosa , some genes of WRKY family were also differentially accumulated amoung the xylem tissues of tension wood, opposite wood, and normal wood ( Chen et al, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…Eleven genes that may encode transcription factors were identified, eight of which belong to the WRKY family. Our findings on differential expression of many genes encoding transcription factors are supported by previous investigations on other trees, such as rubber tree ( Meng et al, 2021 ) and Populus tomentosa ( Chen et al, 2015 ). In P. tomentosa , some genes of WRKY family were also differentially accumulated amoung the xylem tissues of tension wood, opposite wood, and normal wood ( Chen et al, 2015 ).…”
Section: Discussionsupporting
confidence: 90%
“…Notably, TFs are a class of protein molecules that synergistically regulate multiple genes in the biosynthetic pathway at the transcriptional level. The phenylpropanoid biosynthesis pathway is very complex and involves a wide variety of enzymes, sometimes not controlled by one or two key enzymes, and TFs perform macroscopic functions in regulating the flow of phenylpropanoid biosynthesis through the synergistic regulation of multiple genes in the biosynthetic pathway ( Meng et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phenylpropanoid pathway is regulated by TFs such as WRKY, MYB, bZIP, NAC etc. ( Meng et al., 2021b ). In the current study also, we have observed upregulation of WRKY and MYB across both the time points.…”
Section: Discussionmentioning
confidence: 99%